Association of Low-Density Lipoprotein Receptor-Related Protein 1 and Its rs1799986 Polymorphism With Mild Cognitive Impairment in Chinese Patients With Type 2 Diabetes - Cao, Wuyou; Tian, Sai; Zhang, Haoqiang; Zhu, Wenwen; An, Ke; Shi, Jijing; Yuan, Yang; Wang, Shaohua (Frontiers in Neuroscience, 2020)
Background Low-density lipoprotein receptor-related protein 1 (LRP1) is involved in cerebral glucose metabolism and amyloid-β clearance. This study aimed to investigate the pathogenetic roles of LRP1 and its rs1799986 polymorphism in mild cognitive impairment (MCI) among patients with type 2 diabetes mellitus (T2DM). Methods A total of 166 Chinese patients with T2DM were enrolled and divided into two groups according to Montreal Cognitive Assessment (MoCA) scores. Neuropsychological tests were performed. Soluble LRP1 (sLRP1) levels were assessed using enzyme-linked immunosorbent assay, and the genotype of LRP1 rs1799986 was detected using the Sequenom method. Results Diabetic patients with MCI (n = 60) exhibited significantly lower plasma sLRP1 levels (p = 0.033) and worse glucose control (p = 0.009) than the healthy cognition controls (n = 106). Multivariate regression analysis revealed plasma sLRP1 levels [odds ratio (OR) = 0.971, p = 0.005] and HbA1c (OR = 1.298, p = 0.003) as a risk factor for MCI in diabetic patients, in addition to insulin use and hypertension. However, there was no association between plasma sLRP1 levels and HbA1c. After adjusting for age, sex, and education level, plasma sLRP1 levels in the MCI group were negatively correlated with Stroop Color Word Test B number (r = −0.335, p = 0.011), which represents selective attention, cognitive flexibility, and processing speed. Additionally, patients with T2DM carrying the T allele of LRP1 rs1799986 showed higher Auditory Verbal Learning Test (AVLT) delayed recall scores (p = 0.025). Conclusion Decreased plasma sLRP1 levels are associated with MCI, particularly with attention dysfunction, in patients with T2DM. Moreover, the T allele of LRP1 rs1799986 may decrease susceptibility to MCI. Further studies with large cohorts should be designed to elucidate the roles of LRP1 in hyperglycemia-induced cognitive decline.